Silica nanoparticles induce spermatocyte cell autophagy through microRNA-494 targeting AKT in GC-2spd cells. (December 2019) - Ren, Lihua; Liu, Jianhui; Zhang, Jin; Wang, Ji; Wei, Jialiu; Li, Yanbo; Guo, Caixia; Sun, Zhiwei; Zhou, Xianqing
Abstract: Researches had shown that silica nanoparticles (SiNPs) could reduce the quantity and quality of sperms. However, chronic effects of SiNPs have not been well addressed. In this study, mice spermatocyte cells (GC-2spd cells) were continuously exposed to SiNPs (5 μg/mL) for 30 passages and then the changes of microRNA (miRNA) profile and mRNA profile were detected. The function of miRNAs was verified by inhibitors to explore the regulation role of miRNAs in reproductive toxicity induced by SiNPs. The results showed that SiNPs induced cytotoxicity, and activated autophagy in GC-2spd cells. SiNPs led to a total of 1604 mRNAs (697 up-regulated and 907 down-regulated) and 15 miRNAs (6 up-regulated such as miRNA-138 and miRNA-494 and 9 down-regulated) with different expression in GC-2spd cells. The combined miRNA profile and mRNA profile showed that 415 mRNAs with different expression in 5 μg/mL SiNPs group were regulated by miRNA. Furthermore, our study demonstrated that SiNPs decreased the expressions of AKT mRNAs. Moreover, SiNPs had an activation effect on the AMPK/TSC/mTOR pathway. However, inhibitor of miRNA-494 could attenuate the expression levels of AMPK, TSC, LC3Ⅱ and alleviate the decreased of AKT, mTOR, p-mTOR induced by SiNPs. The above results suggested that the low-dose SiNPs exposure could promote autophagy by miRNA-494 targeting AKT, thereby activating AMPK/TSC/mTOR pathway in GC-2spd cells. MiRNA-494 is an important regulator of autophagy by targeting AKT, which provides new evidence for the male reproductive toxicity mechanism of SiNPs. Graphical abstract: Image 1 Highlights: MiRNA-494 activated AMPK/TSC/mTOR pathway by targeting inhibition the expressions of AKT. Exposure to low-dose SiNPs for long-term could induce reproductive toxicity by mediating the alteration of miRNAs in GC-2spd cells. Abstract : The main finding: MiRNA-494 is an important regulator of autophagy by targeting AKT, which provides new evidence for male reproductive toxicity mechanism of SiNPs.